Ekspresi Tabu Bahasa Wanita pada Status dan Komentar di Jejaring Sosial Instagram - Wika Wahyuni; Mahyuni Mahyuni; Johan Mahyudi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This research is based on differences in the variety of languages ​​of women and men in society. The research is focused on the taboo language used by women in written form on the Instagram social network. The use of taboo language by men is more accepted in society. The formulation of the premise of this study is to determine the forms of female taboo expressions on Instagram. This research is a qualitative descriptive study that is based on the use of taboo language on Instagram. The purpose of this study is to describe the forms of taboo expressions written by women on Instagram. The process of data collection was done by referring to the record anddocumentation method. Data were analyzed using taboo theory according to Wijana (2006) and Timothy Jay (1996). The results of the analysis showed that women use taboo language expressions which are vulgar, sexually harassing, name-calling and insulting.